2013
DOI: 10.3109/01443615.2012.741150
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of molar pregnancies in Malaysia: A tertiary centre experience

Abstract: Gestational trophoblastic disease (GTD) is a common problem among Asian ethnics. A total of 102 women with molar pregnancies between 1 January 2005 and 31 December 2010, were analysed. The aim of the study was to determine the outcome of all molar pregnancies in our institution. The local incidence of molar pregnancy was 2.6 per 1,000 deliveries. A total of 48 women (47.1%) had complete hydatidiform mole and another 54 (52.9%) had partial mole. The mean age of the women with molar pregnancies was 32.0 ± 7.9 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
7
10
0
Order By: Relevance
“…Our study had shown that, 78.95% patients of GTD were in first trimesters of pregnancy at the time of diagnosis, which was similar to the study done by Nirmala CK et al(2013) 17 and Simms-Stewart D et al (2013) 18 reported the median gestational age by date as 12 wks.…”
Section: Resultssupporting
confidence: 90%
“…Our study had shown that, 78.95% patients of GTD were in first trimesters of pregnancy at the time of diagnosis, which was similar to the study done by Nirmala CK et al(2013) 17 and Simms-Stewart D et al (2013) 18 reported the median gestational age by date as 12 wks.…”
Section: Resultssupporting
confidence: 90%
“…18 Although the studies by Mourali et al 17 and Nirmala et al 18 did not compare gestational age at diagnosis between women who did and did not develop postmolar GTN, the gestational age at diagnosis in patients with partial molar pregnancies in these studies is similar to our experience. In addition, our findings together with those of Mourali et al 17 and Nirmala et al 18 highlight that many women are now diagnosed with a partial molar pregnancy in the first trimester. The routine use of the first trimester ultrasonography is likely the driving factor in this observation.…”
Section: Discussionsupporting
confidence: 82%
“…Early marriage and early conception may be the reason for lower mean age in our study. 12,13 The occurrence of a molar pregnancy strongly correlates with maternal age especially for women younger than 16 years and even more pronounced for those above 45 years. 14 women had a uterus larger than dates the but in our study in 54.6% patients uterine height was more than the period of gestation and this may be because of late presentation.…”
Section: Resultsmentioning
confidence: 99%